Sex differences in the lateralization of sustained electrophysiological response to 40 Hz clicks in typically developing preschoolers - Victoria Manasevich; Anastasia Neklyudova; Olga Sysoeva (Scientific Reports)
Abstract Two EEG-responses to periodical auditory 40-Hz stimulation – auditory steady-state response (ASSR) and sustained wave (SW) – are important neurophysiological correlates of temporal and spectral aspects of auditory perception, respectively. However, little is known about the sex difference of their development in children of 3–6 years, the period of extensive language acquisition. We registered a 32-channel electroencephalogram (EEG) while 500-ms 40-Hz click trains (n = 150) were presented to 57 typically developing children (27 females). We also assessed total language skill, expressive and receptive speech abilities, the perception of speech in noise and pseudowords repetition. 40-Hz ASSR was not very clearly expressed in our sample but showed developmental increase for both boys and girls. Topography of SW showed significant right-hemisphere predominance in boys, while girls had more symmetric response. On a subsample of boys (n = 14) we also found that the laterality index of SW correlated with speech in noise repetition score: the greater rightwarded the laterality was, the worse boys repeated words in noise. Our results are also consistent with the findings of greater lateralization of some components of EEG-activity in men.